Água ozonizada (O3) no controle de Salmonella enterica Typhimurium em carne resfriada de jacaré do Pantanal (Cayman crocodilus yacare) - Lôbo, Antonio Sergio Marques Teles (2013)
This study aimed to evaluate the efficiency of ozone O3 in the form of ozonated water to control Salmonella enteric Typhimurium and its interference for the period of validityof the commercial filets from the tail of Alligator-of-Pantanal (Caiman crocodiles yacare) bred in captivity, and that the program of the Good Manufacturing Practices of the property is suitable for ensuring the safety of meat produced. After the slaughter and chilling of carcasses, 120 samples of tail fillet (200g each) were randomly separated.The 120 samples were divided into four groups of 30 samples each: GI – without inoculation of Salmonella enteric Typhimurium, and without treatment with Ozone, remaining in the original packaging throughout the experiment. GII - inoculated with Salmonella enteric Typhimurium (5.109) + immersion in ozonated water at room temperature (4,0 ppm, 5 minutes), GIII - inoculated with Salmonella enteric Typhimurium (5.109) without treatment with ozone and GIV - inoculated with Salmonella enteric Typhimurium (5.109) + immersion in ozonated water (4,0 ppm, 5 minutes) chilled to 2° C. The samples after treated, were inserted in packs of highdensity polyethylene, sealed and stored at refrigeration temperature (5.5° C) for 20days. From day zero, in every 48 hours (day 0, 2, 4, 6, 8, 10, 12, 14, 16 and 18) three samples of each group were subjected to plating in selective medium for counting the Salmonella enteric Typhimurium and also subjected to physicochemical tests (evidence of cooking, pH, total volatile bases (N-TVB) and Colorimetry (L * a * b *). The results showed that iced ozonated water was effective for the reduction of Salmonella enterica Typhimurium, and also that Salmonella spp. was not found in samples of Group I where ozonated water was not used, so the Good Manufacturing Practices implemented by the establishment may be considered satisfactory. The physico-chemical tests characterized the Alligator tail ́s filets, during the 20 days of the experiment, suitable for consumption without showing any sign of decay, confirming a differential resistance of this meat once it is seafood.